Creative thinking learning of physical education: Can be enhanced using discovery learning model? - Dupri; Nazirun, Novia; Candra, Oki (UIR Press, 2021)
The teacher-centered mindset and teaching methods are still teacher-centered, closing the space toward students to develop their creative thinking abilities. This study aims to determine the thinking skills of students in physical education learning using discovery learning models. This study used a quasi-experiment method and a pretest and posttest control group design. The research sample was obtained by means of random cluster sampling with a sample amount of 70 people. The instrument that used to measure students' creative thinking skills used the Torrance Test of Creative Thinking (TTCT) which before be tested, it has conducted the validity and reliability. The t test was used as the analysis of this study. Discovery learning model is proven to be able to develop students' creative thinking skills when learning physical education. This is proven by the sig value. 0,000 so the discovery learning model in physical education learning will be able to develop creative thinking on students. This learning model must be applied in various fields of education. Research on the same topic should be carried out in the future, with the variability of different educational levels of subjects or educational institutional settings.